Connected in separation a study of the family dynamics and long-distance interpersonal communication relationships of Manila-based OFW families - Rule, Rube Bloom C.
"This thesis examines, using the case study method, the communication dynamics of six Manila-based families of overseas Filipino workers (OFWs) by exploring their face-to-face and mediated interaction. The informants communicate to maintain their connections, to continue to fulfill their specific family roles and to facilitate and monitor family-owned business ventures. Women in OFW families play multiple roles as financial, nurturance and domestic providers for their families while men only perform traditional financial provider and decision-making roles. Gender-based roles in influence the kinds of messages individual informants share with specific family members and the manner they share them. Informant-family members with the most access and skills to communication tools serve as mediators and/or gatekeepers to communication between their left-behind families and OFW family members abroad. OFW informant-families that communicate using a variety of communication tools that are closer in quality to face-to-face contact are able to have longer, more frequent interactions and more dynamic relationships."